Concentrating solar assisted biomass-to-fuel conversion through gasification: A review - Xu, Dequan; Gu, Xinzhuang; Dai, Yanjun (Frontiers in Energy Research, 2023)
Solar energy, the most abundant and exploitable renewable energy resource, is regarded as a major energy source for the future. Nevertheless, solar irradiation is characterized by relatively low energy density, intermittency and uneven distribution. Storage of solar energy for usage during non-solar times is required to match supply and demand rates in today’s society. In this context, the application of solar energy for converting into storable, transportable, and energy-dense fuels (i.e., solar fuels) is an attractive option, with the advantage of contributing to promoting the commercialization of solar power technologies. Solar assisted biomass gasification is a promising pathway to produce solar fuels. With concentrated solar energy providing reaction heat, carbonaceous materials can be converted to high grade syngas, which could be further synthesized into useful hydrocarbon fuels. In such process, solar energy is stored in a chemical form, with solar spectrum fully utilized. Compared with autothermal biomass gasification, the usage of high-flux concentrated solar radiation to drive endothermic gasification reactions improves energy efficiencies, saves biomass feedstocks, and is relatively free of combustion by-products. This review presents a comprehensive summary of solar assisted biomass gasification, including concentrating solar technology, fundamentals of solar biomass gasification, state-of-the-art solar gasifier designs, strategies for solar intermittence management, and downstream applications.